Integrasi Faktor Manusia dalam Tata Kelola Keamanan Siber Berbasis Cloud: Studi Pengembangan Framework - Kevin Maulana Firdaus (Jurnal Manajemen Teknologi Informatika, 2025)
This study aims to develop a cloud-based cybersecurity governance framework that integrates human factors as a central element. A qualitative approach with a conceptual framework development design was employed through literature review, needs analysis, People–Process–Technology model design, and conceptual implementation simulation. The results indicate that integrating human factors, governance processes, and technical controls into a unified framework provides a more holistic and adaptive approach to cybersecurity management in digital organizations. The proposed framework positions humans as active actors in the security system, supported by policies, standard operating procedures, and cloud security technologies. This study contributes theoretically to the development of cybersecurity governance research and practically serves as an initial reference for organizations in designing human-centered cybersecurity strategies in cloud environments.